Karakteristik Subsemiring Fuzzy - Saman Abdurrahman (Jurnal Fourier, 2020)
Dalam tulisan ini, didefinisikan subsemiring fuzzy dan menyelidiki sifat yang terkait. Selain itu, diperkenalkan konsep subsemiring yang diinduksi dari level subset. Akhirnya, karakteristik subsemiring fuzzy diperoleh. [In this paper, we define the notion of fuzzy subsemiring and investigate the related properties. Moreover, we introduce the idea of a subsemiring induced from the level subset. Finally, a characterization of a fuzzy subsemiring is obtained.]